Analysis of Elementary School Students' Creativity Through STEAM-Based Science Activities in Prototype Development - Veronica Resty Panginan; Susianti; Yusrina (Program Studi PGSD Universitas Madako Tolitoli, 2026)
This study addresses the limited development of elementary school students’ creativity in science learning, particularly in higher-order cognitive skills such as creation. It aims to analyze students’ creativity through STEAM-based science activities in prototype development. The research employed a qualitative descriptive approach using a multiple-case study design, involving 10–15 students aged 6–12 years. Data were collected through direct observation and structured interviews during two engineering-themed science activities, namely Brush Bot and X-Ray projects. The findings indicate a significant improvement in students’ creativity, with 80% in the Brush Bot activity and 83% in the X-Ray activity reaching highly creative levels, characterized by artistic quality and functional outcomes. Creativity was assessed through fluency, originality, flexibility, and elaboration, all of which demonstrated very good performance. The results further reveal that STEAM-based activities effectively foster curiosity, independence, and a shift from output-oriented to outcome-oriented thinking. These findings imply that integrating STEAM-based prototype development into elementary science learning constitutes an effective pedagogical strategy to enhance students’ creativity and higher-order thinking skills.